(untitled) (Journal of Engineering, 2009)
Light naphtha treatment was achieved over 0.3wt%Pt loaded-alumina, HY-zeolite and Zr/W/HY-zeolite catalysts at temperature rang of 240-370°C, hydrogen to hydrocarbon mole ratio of 1-4 0.75-3 wt/wt/hr, liquid hourly space velocity (LHSV) and at atmospheric pressure. The hydroconversion of light naphtha over Pt loaded catalyst shows two main reactions; hydrocracking and hydroisomerization reactions. The catalytic conversion of a light naphtha is greatly influenced by reaction temperature, LHSV, and catalyst function. Naphtha transformation (hyroisomerization, cracking and aromatization) increases with decreasing LHSV and increasing temperature except hydroisomerization activity increases with increasing of temperature till 300°C then began to decrease due to the formation of hydrocracking reaction. The investigation of Pt containing catalysts under study shows a very high hydrogenlysis activity , due to presence of metal component (i.e. Zr, W) which enhances the rate of paraffin isomerization and cracking.The hyroisomerization and the hydrocraking activities can be arranged as follows,.Pt/Zr/W/HY > Pt/HY > Pt/γ-Al2O3 The results showed that, Pt/γ-Al2O3 has higher activity for the direct dehydrogenation of C6 and C7 paraffin’s present in naphtha to aromatics than Pt/HY and Pt/Zr/W/HY. This was due to pore volume catalyst ,the aromatics compounds increased as the pore volume increased.